InDesign CS4 bible - Gruman, Galen (Bible., 2009)
"The soup-to-nuts guide on everything InDesign users need to know about the much-anticipated CS4 release! Learn how to edit Photoshop, Illustrator, and PDF files from within InDesign; export documents in HTML for publication on CD-ROM or the Web; tap the power of multiple layers and master pages; optimize InDesign for efficient project workflow; take advantage of dynamic spell-checking; and more"--Resource description page.